COVID-19 Outbreak: How Informed Were We? Newspaper Coverage of Health and Nutrition Related Information in Nigeria - Iheme, Gideon; Ezenwa, Happiness; Nzeagwu, Ogechi; Onwubuya, Netochukwu; Uche, Precious; Makanjuola, Okeoghene; Ngharamike, Stellamaris (Current developments in nutrition, 2022)
This study aimed to analyze the reporting/transmission of COVID-19 related nutrition and health information by Nigerian newspapers during the COVID-19 outbreak. This secondary/desk research design employed a quantitative content analysis of all articles from two widely read national newspapers published in April and May 2020. Inter-coder reliability test was done by two independent coders to improve the consistency and validity of findings. The unit of analysis comprised all COVID-19 information reported on the news stories, features, editorials and opinions column. Results revealed that COVID-19 information received a fair (more than a tenth) coverage of all articles reported in Nigerian media. COVID 19 statistics/updates (44.8–53.5%) and food/palliative distribution/support (44.2–44.8%) dominated the news article column of Nigerian media, with a little attention (2.3–10.4) on health and nutrition awareness/sensitization. It was observed that COVID-19 reports on feature article segment of Nations and Punch newspapers bothered on covid-19 protocol enforcement (26.8%), COVID-19 impact on international relations (9.7%), COVID-19 new waves/strain awareness/description (7.3%), health sector role in COVID-19 containment (9.8%) whereas COVID-19 and food/nutrition recorded minimal appearance (4.9%). Food/nutrition-related COVID-19 reports were missing on the front page, editorial, international news and advertisement/business segment of the reviewed newspapers. Overall data revealed that this COVID-19 information were predominantly COVID-19 statistics/case updates, food/palliative distribution update, impact of COVID-19 on the economy and other sectors while in-depth reporting of health and nutrition related COVID-19 awareness was lacking. Prompt sensitization and education on emerging issues of public health is the ethical responsibility of the print media to the public. None.